2021
DOI: 10.1186/s12872-021-01868-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prescribing practice of guideline-directed medical therapy among ambulatory chronic heart failure patients

Abstract: Background Studies have demonstrated that heart failure (HF) patients who receive direct pharmacist input as part of multidisciplinary care have better clinical outcomes. This study evaluated/compared the difference in prescribing practices of guideline-directed medical therapy (GDMT) for chronic HF patients between two multidisciplinary clinics—with and without the direct involvement of a pharmacist. Methods A retrospective audit of chronic HF pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 66 publications
5
4
0
Order By: Relevance
“…In the present study, IHD was consistently associated with a higher prescription score irrespective of HF phenotype. These findings are consistent with a previous study in which IHD was found to be a positive predictor of β-blocker prescription in patients with HFrEF and HFpEF [5].…”
Section: Factors Associated With Suboptimal Prescription Scoressupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, IHD was consistently associated with a higher prescription score irrespective of HF phenotype. These findings are consistent with a previous study in which IHD was found to be a positive predictor of β-blocker prescription in patients with HFrEF and HFpEF [5].…”
Section: Factors Associated With Suboptimal Prescription Scoressupporting
confidence: 93%
“…The baseline characteristics of patients with HF were similar to previously published studies [4,5]. Patients with HFrEF were more likely to be younger and have ischaemic cardiovascular diseases, and less likely to have hypertension compared to patients with HFpEF [4,5]. However, diabetes was observed more frequently in patients with HFpEF compared to HFrEF and HFmrEF (p = 0.037) in the present study, whereas in the CHARM and ESC-HF long-term registry cohorts, the proportion of patients with diabetes was similar across all three phenotypes (p = 0.14 and p = 0.71, respectively) [14,15].…”
Section: Baseline Characteristics and Prescription Pattern Of The Dru...supporting
confidence: 81%
See 3 more Smart Citations